Toxins MazF and MqsR cleave Escherichia coli rRNA precursors at multiple sites. Issue 1 (2nd January 2017) - Mets, Toomas; Lippus, Markus; Schryer, David; Liiv, Aivar; Kasari, Villu; Paier, Anton; Maiväli, Ülo; Remme, Jaanus; Tenson, Tanel; Kaldalu, Niilo
ABSTRACT: The endoribonuclease toxins of the E. coli toxin-antitoxin systems arrest bacterial growth and protein synthesis by targeting cellular mRNAs. As an exception, E. coli MazF was reported to cleave also 16S rRNA at a single site and separate an anti-Shine-Dalgarno sequence-containing RNA fragment from the ribosome. We noticed extensive rRNA fragmentation in response to induction of the toxins MazF and MqsR, which suggested that these toxins can cleave rRNA at multiple sites. We adapted differential RNA-sequencing to map the toxin-cleaved 5′- and 3′-ends. Our results show that the MazF and MqsR cleavage sites are located within structured rRNA regions and, therefore, are not accessible in assembled ribosomes. Most of the rRNA fragments are located in the aberrant ribosomal subunits that accumulate in response to toxin induction and contain unprocessed rRNA precursors. We did not detect MazF- or MqsR-cleaved rRNA in stationary phase bacteria and in assembled ribosomes. Thus, we conclude that MazF and MqsR cleave rRNA precursors before the ribosomes are assembled and potentially facilitate the decay of surplus rRNA transcripts during stress.